KOMPUTASI GUI-R UNTUK PEMODELAN REGRESI NONPARAMETRIK BIRESPON POLINOMIAL LOKAL PADA PENGARUH SUKU BUNGA BI TERHADAP INDEKS HARGA SAHAM GABUNGAN DAN KURS USD - Rudi Saputro Setyo Purnomo; Suparti Suparti; Sudarno Sudarno (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2020)
Economy is one of important indicator of development country. Capital market is one of important tool in economy. The development of the capital market in Indonesian can be seen based on the composite stock price index (CSPI). Other than capital market, international trade is an important tool in the economy. Existence of the international trade generates exchange rate, one of which is USD exchange rate. Exchange rate can be increased and weakened, so it’s stability needs to be maintained. One of the factor that can influence CSPI and USD exchange rate is the BI interest rate. To be able to predict the value of CSPI and USD exchange rate then do the birespon regression modelling because between CSPI and USD exchange rate there are relationship. The regression model approach which used in this research is local polynomial. This approach has high adaptability with data. To make the modelling easier so this research arrange Graphycal User Interface (GUI) by using R software. The local polynomial birespon regression is applied to CSPI and USD exchange rate data based on BI interest rate by using GUI. The optimal modal is obtained by General Cross Validation (GCV) optimation. The optimal model is model by combination of sequences two and three, bandwidths 6 and 2,7, and local points 5,75 and 6. The value of R Square is 66,68% and the mean absolute percentage error (MAPE) is 4,0798%. This MAPE shows that the optimal model has very high accuration in prediction the data because this value of MAPE less than 10%.Keywords: CSPI, USD exchange rate, BI interest rate, birespon, local polynomial, GUI.